Pengaruh Kemampuan Kerja, Tingkat Pendidikan Dan Kompensasi Terhadap Kinerja Karywan Pada CV.Aliv Media Informatika - Devi Puspita Sari; Sonny Subroto M L; Umi Nadhiroh (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This research is to determine the influence of work ability variables (X1), education level (X2) and compensation (X3) on employee performance (Y) of CV Alif Media Informatics. Quantitative type. The data collection techniques used are primary data and secondary data. Sample selection used the saturated sampling method, the total sample was 34 respondents at CV Alif Media Informatika. This research data was obtained through questionnaires, interviews and literature studies.The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The results of the research obtained the multiple linear regression equation Y= -1.986 + 1.130X1 + 0.781X2 + 0.715X3 and the t test results of the work ability variable had a partially significant effect on employee performance. t test results: The educational level variable has a partially significant effect on employee performance. The results of the t test of the compensation variable have a partially significant effect on employee performance. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that work ability, level of education and compensation simultaneously and significantly influence employee performance.